2001
DOI: 10.1037/0278-7393.27.5.1223
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation between syntactic and semantic processing during idiom comprehension.

Abstract: Syntactic and semantic processing of literal and idiomatic phrases were investigated with a priming procedure. In 3 experiments, participants named targets that were syntactically appropriate or inappropriate completions for semantically unrelated sentence contexts. Sentences ended with incomplete idioms (kick the...) and were biased for either a literal (ball) or an idiomatic (bucket) completion. Syntactically appropriate targets were named more quickly than inappropriate ones for both contextual biases, sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
73
0
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(84 citation statements)
references
References 41 publications
8
73
0
3
Order By: Relevance
“…In contrast, we substituted words with semantically related or unrelated words, such that in the anomalous conditions the word in question was never actually presented, which likely emphasizes top-down effects such as anticipation. This explanation is supported by the observation that, in the previously discussed study by Peterson et al (2001), the final words of the idioms were also not presented but had to be produced by the participants themselves. In line with our results, this study did not report evidence for literal word meaning activation.…”
Section: Literal Word Meaning Activation In Idioms As a Bottom-up Promentioning
confidence: 53%
See 1 more Smart Citation
“…In contrast, we substituted words with semantically related or unrelated words, such that in the anomalous conditions the word in question was never actually presented, which likely emphasizes top-down effects such as anticipation. This explanation is supported by the observation that, in the previously discussed study by Peterson et al (2001), the final words of the idioms were also not presented but had to be produced by the participants themselves. In line with our results, this study did not report evidence for literal word meaning activation.…”
Section: Literal Word Meaning Activation In Idioms As a Bottom-up Promentioning
confidence: 53%
“…However, other studies have demonstrated a lack of literal word meaning activation in idioms. Peterson, Burgess, Dell, and Eberhard (2001) found that, when participants were asked to complete predictable sentence contexts with a spoken target word, there was a concreteness effect in literal sentences (shorter speech onset latencies for abstract than concrete target words) but not in idioms, suggesting that literal word meanings were not processed. Furthermore, in an fMRI study, somatotopically distributed activation of the motor system was observed for action verbs in isolation (e.g., grab/kick), in literal sentences (e.g., The fruit cake was the last one so Claire grabbed it), but not in idioms in sentences (e.g., The job offer was a great chance so Claire grabbed it; Raposo, Moss, Stamatakis, & Tyler, 2009).…”
Section: Activation and Unification Of Literal Word Meanings In Idiommentioning
confidence: 98%
“…The data Whether the constituents of clichés lose their semantic value-that is, whether or not they are fully processed as individual words when occurring in the cliché-is a different issue. There are various pieces of evidence suggesting that the individual words of conventional expressions are indeed analyzed (Konopka & Bock, 2009;Peterson, Burgess, Dell, & Eberhard, 2001;Trueswell & Kim, 1998;Van de Voort & Vonk, 1995); we will return to this point later. But even if it should turn out that the individual components of clichés are not fully analyzed during string processing, in these expressions it is still the case that the meaning is the result of the composition of their individual words.…”
Section: Resultsmentioning
confidence: 94%
“…Using a sentence-priming procedure, Peterson et al (2001) had their participants hear sentence primes ending with incomplete idioms. Sentences were biased toward a literal (e.g., the soccer player slipped when tried to kick the .…”
Section: Resultsmentioning
confidence: 99%
“…There is, rather, a continuum between wholly memorized and wholly rule-based constructions, with most forms falling somewhere between these extremes (Langacker, 1987). Hence, apparently abstract syntactic constructions may be associated with particular lexis (Hoey, 2005;Hunston & Francis, 2000;Stefanowitsch & Gries, 2003) and apparently memorized forms (such as idioms) may be subject to syntactic processing and variation (Gibbs, Nayak, & Cutting, 1989;Peterson, Burgess, Dell, & Eberhard, 2001). …”
Section: Introductionmentioning
confidence: 99%